Is dietary taurine supplementation beneficial for gilthead seabream (Sparus aurata) larvae? - Pinto, W. (2014)
This study evaluated the effect of dietary taurine supplementation on the growth performance and methionine metabolism of gilthead seabream larvae. For this purpose, a growth experiment was carried out in which seabream larvae were fed upon rotifers supplemented with “blank” or taurine-enriched liposomes. A complementary trial was also done in which seabream larvae fed with live prey were subsequently tube-fed a solution containing a L-[U-14C] methionine with or without a taurine supplement. Results from the growth experiment showed that rotifers were successfully enriched with taurine, but no effects were observed on larval growth performance, survival or amino acid composition. Furthermore, dietary taurine supplementation did not result in an increase of larval taurine levels, a factor that may have been determinant for the absence of effects observed on growth performance. In the tube-feeding trial, results showed that dietary taurine supplementation led to an increase of methionine retention in larvae. These findings suggest the existence of an active taurine biosynthesis pathway for gilthead seabream during the larval stage. Hence, gilthead seabream may not be dependent on dietary taurine to maintain the taurine body pool, since it may convert taurine from methionine if required. Taken together, the results from this study indicate that dietary taurine supplementation does not seem to enhance the larval growth performance in fish species able to biosynthesise taurine during this stage, which seems to be the case of gilthead seabream. However, this study also showed that in these species, dietary taurine supplementation may ultimately affect larval metabolism by increasing methionine availability for several important physiological purposes, contributing to a better understanding on the role of taurine during the early life stages of fish development.